Elastosis Perforans Serpiginosa in a patient with Down syndrome treated with imiquimod 5% cream. - Pernille Axèl Gregersen; Birgitte Stausbøl-Grøn; Mette Ramsing; Mette Sommerlund (PAGEPress Publications, 2010)
Elastosis Perforans Serpiginosa (EPS) is a rare skin disease characterised by hyperkeratotic papules, transepidermal elimination of abnormal elastic fibres, and focal dermal elastosis. The aetiology is unknown, but an association with underlying systemic disorders, including Down syndrome has been described. Treatment is often difficult. A 45-year old man with Down syndrome presented with symmetrical annular elements on forearms and femora. The elements were erythematous with atrophic hypopigmented central healing and peripherally, infiltrated keratotic papules with desquamation. A punch biopsy showed the classical histopathologic features of EPS. We found no clinical signs of cerebrovascular or cardiovascular disease. We initiated topical therapy with imiquimod 5% cream once a day for 6 weeks followed by 3 times weekly for 4 weeks to a single element. As regression of EPS was observed and the patient tolerated the therapy well, treatment of other lesions was commenced, and further regression was seen.